Analysis of Legal Protection for South Sulawesi Sepaktakraw Athletes’ Welfare According to Law No. 11 of 2022 of the Republic of Indonesia - Syahrir, Alfian; Sudirman, Sudirman; Nawir, Nukhrawi; Hudain, Muh. Adnan; Arfanda, Poppy Elisano (UNIVERSITAS NEGERI MAKASSAR, 2024)
The purpose of the study was to determine the legal protection for the welfare of sepak takraw athletes in South Sulawesi according to Law No. 11 of 2022. This study is a qualitative study of document studies. This study uses a single variable, namely legal protection for the welfare of sepak takraw athletes. The population in this study were all sepak takraw athletes in South Sulawesi totaling 22 athletes and 2 athlete coaches. The research data were obtained by conducting an interview test. The data analysis technique, namely by collecting data using document studies and field studies, found that legal protection for the welfare of athletes in South Sulawesi has been realized for several athletes. It can be concluded that 1) Analysis of legal protection for the welfare of sepak takraw athletes in South Sulawesi according to Law No. 11 of 2022 has been implemented but has not been maximized. It is hoped that in the future the government will pay more and even more attention to South Sulawesi athletes, especially the Sepaktakraw sport. 2) Some athletes still do not know what their rights and authorities are as athletes. In the future, researchers hope that athletes can learn more deeply about their rights and obligations as professional athletes. 3) On average, athletes tend to be more concerned about their age and jobs. In the future, athletes hope that the government will guarantee suitable jobs and decent housing.